NOVEL QOZAN “KEMBALIKAN HUTANKU” KARYA IMOGAIL ZAM ZAMI DJALALUDDIN DALAM KAJIAN EKOKRITIK (NOVEL QOZAN ”RESTORE MY FOREST” BY IMOGAIL ZAM ZAMI DJALALUDDIN IN AN ECOCRITICAL STUDY) - Suryanti Suryanti (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2023)
AbstractQozan Novel "Return My Forest" by Imogail Zam Zami Djalaluddin in Ecocritical Studies. This study aims to represent the form of the environment natural, describe exists damage of environment nature, describes the form of preserving the natural environment, describes the form of local wisdom and the role of the community in preserving the natural environment in Qozan's novel "Return My Forest" by Imogail Zam Zami Djalaluddin. The method used is descriptive method qualitative. The data source in this research is Qozan's novel "Return My Forest" by Imogail Zam Zami Djalaluddin. Collecting data in this study using the technique of literature study. The results of this study found 81 citations of ecocritical studies, including representations of the natural environment, forms of damage to the natural environment, forms of natural environment preservation, and forms of local wisdom in Central Sulawesi. The representations of the natural environment includes the natural environment in the forest (20 citations) and the natural environment on the beach (24 citations). The manifestation of damage to the natural environment consists of 3 components, namely water, air and land, with 12 citations. The manifestation of natural environment sustainability in coastal areas is 6 citations.  The form of local wisdom is in the form of customs that are attached to the indigenous people as many as 11 citations and the regional language used as everyday language as many as 8 citations.Key words: eco-criticism, literature, novel, Qozan novel AbstrakNovel Qozan “Kembalikan Hutanku” Karya Imogail Zam Zami Djalaluddin dalam Kajian Ekokritik. Penelitian ini bertujuan merepresentasikan wujud lingkungan alam, mendeskripsikan wujud kerusakan lingkungan alam, mendeskripsikan wujud kelestarian lingkungan alam, mendeskripsikan wujud kearifan lokal dan peran masyarakat dalam menjaga kelestarian lingkungan alam dalam novel Qozan “Kembalikan Hutanku” karya Imogail Zam Zami Djalaluddin. Metode yang digunakan adalah metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah novel Qozan “Kembalikan Hutanku” karya Imogail Zam Zami Djalaluddin. Pengumpulan data dalam penelitian ini menggunakan teknik studi pustaka. Hasil penelitian ini ditemukannya kajian ekokritik sebanyak 81 kutipan, meliputi representasi lingkungan alam, wujud kerusakan lingkungan alam, wujud kelestarian lingkungan alam, dan wujud kearifan lokal yang ada di Sulawesi Tengah. Representasi lingkungan alam meliputi lingkungan alam di hutan sebanyak 20 kutipan dan lingkungan alam di pantai sebanyak 24 kutipan. Wujud kerusakan lingkungan alam terdiri dari 3 komponen, yaitu air, udara, dan tanah sebanyak 12 kutipan. Wujud kelestarian lingkungan alam di daerah pantai sebanyak 6 kuitpan. Wujud kearifan lokal berupa adat istiadat yang melekat pada penduduk asli sebanyak 11 kutipan dan bahasa daerah yang digunakan sebagai bahasa sehari-hari sebanyak 8 kutipan.Kata-kata kunci: ekokritik, sastra, novel, novel Qozan